Determinants of change in the inequality and associated predictors of teenage pregnancy in Uganda for the period 2006– 2016: analysis of the Uganda Demographic and Health Surveys - Wasswa, Ronald; Kabagenyi, Allen; Muhumuza Kananura, Rornald; Jehopio, Joseph; Rutaremwa, Gideon (BMJ Open, 2021)
Teenage pregnancy has become a public health concern in Uganda because of its negative consequences to both the mother and child. The objective of this study was to examine the determinants of change in the inequality and associated predictors of teenage pregnancy in Uganda for the period 2006– 2016. Study design A retrospective national cross-sectional study. Setting Uganda. Participants Uganda Demographic and Health Survey secondary data of only female teenagers aged 15–19 years. The samples selected for analyses were 1936 in 2006; 2048 in 2011 and 4264 in 2016. Outcome measure The primary outcome was teenage pregnancy. Analysis was performed using the logistic regression, equiplots, concentration curve, normalised concentration index, decomposition of the concentration index and Oaxaca-type decomposition. Results The prevalence of teenage pregnancy has seemingly remained high and almost constant from 2006 to 2016 with the risk worsening to the disadvantage of the poor. Household wealth-index, teenagers’ years of education, early sexual debut and child marriage were the main key predictors and contributors of the large inequality in teenage pregnancy from 2006 to 2016. Conclusion Teenage pregnancy is disproportionately prevalent among different subpopulations of adolescent girls in Uganda. We therefore recommend policy actions to sensitise communities and enforcement of child rights and child protection laws to stop child marriages. There is also need to promote girl child education, improving household incomes, and intensifying mass media awareness on the risks of early pregnancies. Further, ensuring that villages have operational adolescent and youth friendly services as well as incorporating sex education and other different adolescent reproductive health programmes in school curriculum will be key measures in reducing the large inequality in teenage pregnancy.
Keywords: Inequality; Predictors of teenage pregnancy; Uganda; Uganda Demographic and Health Surveys